Sites in human nuclei where damage induced by ultraviolet light is repaired: localization relative to transcription sites and concentrations of proliferating cell nuclear antigen and the tumour suppressor protein, p53. - Jackson, D; Hassan, A; Errington, R; Cook, P (1994)
The repair of damage induced in DNA by ultraviolet light involves excision of the damaged sequence and synthesis of new DNA to repair the gap. Sites of such repair synthesis were visualized by incubating permeabilized HeLa or MRC-5 cells with the DNA precursor, biotin-dUTP, in a physiological buffer; then incorporated biotin was immunolabeled with fluorescent antibodies. Repair did not take place at sites that reflected the DNA distribution; rather, sites were focally concentrated in a complex pattern. This pattern changed with time; initially intense repair took place at transcriptionally active sites but when transcription became inhibited it continued at sites with little transcription. Repair synthesis in vitro also occurred in the absence of transcription. Repair sites generally contained a high concentration of proliferating cell nuclear antigen but not the tumour-suppressor protein, p53.